Strategy Analysis of UMKM Development in Jayapura City to Improve Competitiveness in the Local Market - Sujatmiko, Bambang; Zahrati , Zubdatu; Farid, Ibnu; Mahawati, Hemi; Mairina, Catur Liliek; Prahastuti, Ruri Artanti (Universitas Kristen Cipta Wacana, 2024)
Micro, Small, and Medium Enterprises (MSMEs) in Jayapura City play an important role in the local economy, but they face various challenges in increasing their competitiveness in the local market. This study aims to analyze MSME development strategies in order to increase their competitiveness, and explore government support in the process. The approach used is qualitative with in-depth interviews and participant observation as data collection techniques. The results of the study indicate that the main challenges of MSMEs in Jayapura include limited market access, low managerial capacity, and lack of product innovation. However, MSMEs have implemented product differentiation strategies and utilized digital technology for marketing. Government support in the form of training and access to capital is quite helpful, but limited infrastructure and capital procedures are still obstacles. This study provides recommendations for increasing managerial capacity, expanding market access, and utilizing technology to increase the competitiveness of MSMEs in Jayapura City.